2022
DOI: 10.51178/jetl.v4i2.580
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Schoology Learning Media During the Covid-19 Pandemic

Abstract: This study aims to find out how the application and effectiveness of schoology learning media during the Covid-19 pandemic on biology learning outcomes at MTS Al-Wasliyah Tembung. This research is a qualitative research using case study method. The subjects of this study were the vice principal, teachers of science studies, and 85 students of class IX science at MTS Al-Wasliyah Tembung. The instrument used to collect data was by interviewing the vice principal and biology teachers. While the students used a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In the study, meatballs are composed of oyster mushrooms and tempeh flour. Oyster mushrooms are cheap and rich in nutrients such as up to 30% dietary fiber and up to 30.4% protein [3]. Besides, several studies suggested their functional properties on human health, such as lowering cholesterol, preventing diabetes mellitus, and facilitating the digestive system [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, meatballs are composed of oyster mushrooms and tempeh flour. Oyster mushrooms are cheap and rich in nutrients such as up to 30% dietary fiber and up to 30.4% protein [3]. Besides, several studies suggested their functional properties on human health, such as lowering cholesterol, preventing diabetes mellitus, and facilitating the digestive system [4].…”
Section: Introductionmentioning
confidence: 99%
“…Proses pembelajaran yang baik terdiri dari guru sebagai tenaga pendidik dan siswa. Kegiatan belajar mengajar biasanya dilakuakn di sekolah maupun di rumah (Febriani et al, 2022;Siregar, 2022).…”
unclassified